Identification of BSA B1 Bacteria and Its Potency of Purified Cellulase to Hydrolyze Chlorella zofingiensis - Rifqi Zahroh Janatunaim; Radhiyah Mardhiyah Hamid; Ghea Putri Christy; Yekti Asih Purwestri; Woro Anindito Sri Tunjung (Universitas Gadjah Mada, 2015)
Cellulase has been widely used as biocatalyst in industries. Production of cellulase from microorganismshas many advantages such as short production time and less expense. Our previous study indicated that oneof cellulolytic bacteria from digestive tract of milkfish (Chanos chanos), namely BSA B1, showed the highestcellulase activity. The objective of this study was to determine the phylogenetic of BSA B1 strain using 16SrRNA gene sequence. Furthermore, this study also determine the specific activity of purified cellulase from BSAB1 strain and its potency to hydrolyze Chlorella zofingiensis cellulose. Cellulase was purified using ammoniumsulphate precipitation, dialysis, and ion exchange chromatography. The purified cellulase was used to hydrolyzecellulose of C. zofingiensis. The result demonstrated that BSA B1 strain was closely related with Bacillus aeriusand Bacillus licheniformis. The specific activity of the crude enzyme was 1.543 U mL-1; after dialysis was 4.384 UmL-1; and after chromatography was 7.543 U mL-1. Purified cellulase exhibited activity in hydrolyzed both CMCand C. zofingiensis. Compared to commercial cellulase, purified cellulase had lower activity in hydrolyzed CMCbut higher activity in hydrolyzed C. zofingiensis. Ethanol dehydration could potentially increase the reducingsugar yield in cellulose hydrolysis when used appropriately. Morphology of C. zofingiensis cell has changedafter incubation with cellulases and ethanol dehydration indicated degradation of cell wall.